The impacts of social protection benefits on behaviours potentially related to economic growth: A literature review - Luis Henrique Paiva; Santiago Falluh Varella (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
What are the possible impacts of social protection benefits on economic growth? Although the main objective of these benefits is to protect people from poverty, shocks and social risks - and not promote economic growth - this question pervades both the theoretical and the empirical literature on social policy. The main concern is that social protection could have negative effects on certain behaviours associated with economic growth. They could, for instance, negatively affect savings, labour supply and fertility, all potentially relevant factors to induce short- and long-term economic growth. However, they could also lift liquidity constraints that prevent people from investing more in children's education, starting a new business or migrating to a place where there are more opportunities in the labour market. [...]
Keywords: 330; Impacts; social protection; benefits; behaviours; economic growth; literature; review